A Multi-Functional View of Moral Disengagement: Exploring the Effects of Learning the Consequences - Tillman, C. Justice; Gonzalez, Katerina; Whitman, Marilyn V.; Crawford, Wayne S.; Hood, Anthony C. (Frontiers in Psychology, 2018)
This paper takes us beyond the unethical act and explores the use of moral disengagement as a multi-stage, multi-functional regulatory and coping mechanism that not only allows individuals to engage in unethical behavior, but also manage the negative emotions (i.e., guilt and shame) from learning the consequences of such behavior. A resource-based lens is applied to the moral disengagement process, suggesting that individuals not only morally disengage prior to committing an unethical act in order to conserve their own resources, but also morally disengage as a coping mechanism to reduce emotional duress upon learning of the consequences of their actions, which we describe as post-moral disengagement. These assertions are tested using a scenario-based laboratory study consisting of 182 respondents. Findings indicate that individuals will morally disengage in order to commit an unethical act, will experience negative emotions from having learned of the consequences, and then will engage in post-moral disengagement as a coping mechanism. In addition, the findings suggest that guilt and shame relate differently to moral disengagement.